Aktivitas Sosial, Aktivitas Budaya Dan Agama Terhadap Dana Pihak Ketiga Lembaga Perkreditan Desa (LPD) (Case Kabupaten Tabanan Bali) - Gine Das Prena; Luh Gede Putri Kusuma Pekerti (Jurnal Ilmiah Satyagraha, 2019)
This study aimed to determine the existence of social activities, cultural activities, religious activities on third party funds LPD Tabanan Regency in 2017. The study was conducted in all LPD in Tabanan Regency. The method of determining the sample used in this study is the saturated sampling method and obtained 243 LPD that meet the criteria for sampling. The type of data used is in the form of quantitative data, namely LPD financial reports registered throughout Tabanan Regency. The analytical method used is the classic assumption test, multiple regression analysis, analysis of determination, F-Test and t-test. The results of this study indicate that social activities, cultural activities and religious activities have a significant positive effect on LPD third party funds. The implications of this research for rural credit institutions, strived to continue to improve the empowerment of third party funds for social, cultural and religious activities carried out in the village.